URBAN ENTERTAINMENT HUB DI KAWASAN PANTAI INDAH KAPUK - Jefferson Fritzgerald Karnadi; Sutrisnowati Machdijar (Jurusan Arsitektur dan Perencanaan, 2019)
Jakarta as a busy city has an interpretation that describes the city with its density and irregularity. The city is busy inhabited by residents who race against time where city life runs for 24 hours. Jakarta is ranked 25th as a city with a high level of stress, this is possible because Jakarta is the center of government and business center. At the same time, there is an increasing need for Jakarta's entertainment and recreation to release stress in everyday life in urban areas. To eliminate boredom, a person needs to do activities that are different from his daily routine, so that the person can feel refreshed to do the activity well. Shopping is one of the activities carried out by the community to release fatigue. Therefore, a new container created a